PROFILE PNEUMOPATHIC HOSPITALIZED AND SERVED IN PHYSICAL THERAPY SERVICE IN TEACHING HOSPITAL (Fiep Bulletin - online, 2016)
In Brazil respiratory diseases are responsible for over 15% of all admissions, becoming a serious public health problem. The aim of this study was to analyze the profile of lung disease patients treated by chest physiotherapy CCGS service between 2010 to 2011 at the Hospital Santa Cruz, as well as the seasonality of admissions. Retrospective study, conducted through a survey of patient records lung, resulting from the company CCGS Physiotherapy Hospital between 2010 and 2011, where age, gender, clinical diagnosis and time (seasonal) and hospital stay were evaluated. COPD was the most frequent disease (55.3%), followed by pneumonia (28.5%) and pneumonia (16.2), with a median hospital stay of 6.00 (1-38). The higher incidence in this study was COPD, where the majority of admissions occurred during periods of temperature inversions.
Keywords: Lung; epidemiology; hospital physiotherapy service.